WAYS TO IMPROVE PROJECT MANAGEMENT IN THE FIELD OF INFORMATION TECHNOLOGY IN UZBEKISTAN - Olimova Dildora Turginboevna (European Science Publishing, 2025)
This article explores various strategies to enhance project management practices in the information technology sector in Uzbekistan. As the IT landscape rapidly evolves, the need for effective project management becomes increasingly critical for ensuring project success and achieving organizational goals. The analysis identifies key challenges faced by IT project managers in Uzbekistan, including limited resources, inadequate training, and the need for improved communication. By proposing tailored solutions such as adopting Agile methodologies, investing in training programs, and leveraging modern project management tools, this work aims to provide actionable recommendations that can significantly enhance project outcomes in the region's IT industry.
Keywords: Management, management, technology, projects.